2017 IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS) 2017
DOI: 10.1109/iros.2017.8202281
|View full text |Cite
|
Sign up to set email alerts
|

Market-based coordination in dynamic environments based on the Hoplites framework

Abstract: Abstract-This work focuses on multi-robot coordination based on the Hoplites framework for solving the multi-robot task allocation (MRTA) problem. Three variations of increasing complexity for the MRTA problem, spatial task allocation based on distance, spatial task allocation based on time and distance, and persistent coverage have been studied in this work. The Fast Marching Method (FMM) has been used for robot path planning and providing estimates of the plans that robots bid on, in the context of the marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…In our previous work, a study of MRTA in dynamic and noisy environments [18] for spatial task allocation confirmed the effectiveness of our Hoplites-based method [19] as a first step towards deployment of MRTA methods in social environments. In [20], we proposed a humanaware coordination method for MRTA that accounted for the distance overhead of human-aware paths in the local balance function of the robots and allowed for instant collaboration in socially blocking situations.…”
Section: Related Worksupporting
confidence: 70%
See 3 more Smart Citations
“…In our previous work, a study of MRTA in dynamic and noisy environments [18] for spatial task allocation confirmed the effectiveness of our Hoplites-based method [19] as a first step towards deployment of MRTA methods in social environments. In [20], we proposed a humanaware coordination method for MRTA that accounted for the distance overhead of human-aware paths in the local balance function of the robots and allowed for instant collaboration in socially blocking situations.…”
Section: Related Worksupporting
confidence: 70%
“…1 and Fig. 2) for our experiments that enable simulations with similar environmental richness to the real world experiments, as shown in [18].…”
Section: Simulationsmentioning
confidence: 93%
See 2 more Smart Citations
“…This process is ruled by a market-based approach and constitutes the active coordination. For details about our implementation of an Hoplites-based MRTA refer to [18].…”
Section: B Social Multi-robot Coordinationmentioning
confidence: 99%